Effects of the amount and type of fatty acids present in millets on their in vitro starch digestibility and expected glycemic index (eGI). (July 2015) - Annor, George Amponsah; Marcone, Massimo; Corredig, Milena; Bertoft, Eric; Seetharaman, Koushik
Abstract: This study investigated whether the amounts and types of fatty acids present in millet plays a role in its known hypoglycemic properties. In a two part study, the first part involved complexing excess amount (2 mmol/g of starch) of palmitic, oleic and linoleic acids to cooked pearl, finger, proso and foxtail millet starches, subjecting the complexes to in vitro starch digestibility and calculating their expected glycemic index (eGI). The second part of the study consisted of complexing the millet starches with the fatty acids in the amounts present in their respective millet flours. Elaidic acid in equal amounts to oleic acid was also used to ascertain the effects of the cis or trans configuration of the fatty acid on millet starch digestibility. The complex index (CI) of the fatty acids with millet starch increased with increasing level of unsaturation. Significant (p < 0.05) reductions in the in vitro starch digestibility and eGI of the millet starch-fatty acid complexes were observed. Reductions in the starch hydrolysis of the samples were found to be significantly linked to the amounts of the fatty acids added. The presence of unsaturated fatty acids generally resulted in less starch being hydrolyzed. Oleic acid seemed to be a very effective fatty acid in reducing the amount of starch hydrolyzed. Trans oleic acid (elaidic acid) showed to be less efficacious compared to oleic acid in cis configuration. The amount and type of fatty acids interacting with starch plays a significant role in the hypoglycemic property of millet. Highlights: Fatty acids present in millets played a role in their hypoglycemic property. The different amounts of the different fatty acids in millets affected its hypoglycemic property. Oleic acid played a more significant role in reducing the digestibility of millets starches.